Neutrophil activation via β2 integrins (CD11/CD18): Molecular mechanisms and clinical implications - Schymeinsky, Jürgen; Mócsai, Attila; Walzog, Barbara (Thrombosis and Haemostasis, 2007)
Polymorphonuclear neutrophils (PMN) are key components of the innate immunity and their efficient recruitment to the sites of lesion is a prerequisite for acute inflammation. Signaling via adhesion molecules of the β2 integrin family (CD11/CD18) plays an essential role for PMN recruitment and activation during inflammation. In this review, we will focus on the non-receptor tyrosine kinase Syk, an important downstream signaling component of β2 integrins that is required for the control of different PMN functions including adhesion,migration and phagocytosis. The exploration of β2 integrin-mediated Syk activation provided not only novel insights into the control of PMN functions but also led to the identification of Syk as a new molecular target for therapeutic intervention during inflammatory diseases.
Keywords: Integrins; inflammation; leukocyte trafficking / recruitment; signal transduction